Interlanguage Errors Based on the Source of Errors in Indonesian College Students’ Pronunciation - Harunika, Arian Pramesta; Sakhiyya, Zulfa; Hartono, Rudi (Language Circle: Journal of Language and Literature, 2020)
This study aimed to explore the source of IL errors on male and female students’ pronunciation. The participants in this research were ten college students who were participated in an English speech contest organised by English Student Association of UNNES 2019. The ten participants consist of five male and five female students who came from different kinds of University in Indonesia. In this study, the researcher used a descriptive qualitative method to analyze the data by using a video recorder as an instrument to collect the data. The result of this research showed that there were four sources of errors which influenced male and female students in producing IL errors on pronunciation. Those were L1 transfer, different form of plural between L1 and L2, the existence of sounds with the same phonetic features but different in distribution, and English foreign sounds. The second result described that the source of errors on male and female college students was mostly similar, and they had no significant differences. Last result showed that male students made more variation of IL errors on their pronunciation than female students.